Regenerative Chatter in End Milling on Mould Aluminum Alloys - N. M. Zuki, N. M.; M. M., Rahman; M. M., Noor; M., Hafizuddin (2008)
Milling operation is widely used in the manufacturing industry for the metal cutting purpose. For the efficiency of the milling process, high demands on the material removal rate and the surface generation rate are posed. The process parameters, determining these two rates, are restricted by the occurrence of regenerative chatter. Chatter is an undesired instability phenomenon, which causes both a reduced product quality and rapid tool wear. In this paper, the regenerative chatter are predicted during milling process, based on dedicated experiments on both the material behavior of the workpiece material and the machine dynamics. Then, experiments are performed to estimate these chatter occurrence in practice. These experiments show that both the material properties and the machine dynamics are dependent on the spindle speed. The resultants F-T analysis graphs obtained are compared to each other and being analyzed. Finally, a stable combination of machining parameter (spindle rotation speed and depth of cut) is proposed and applied during milling process in order to reduce the tendency of chatter occurrence. This cross linking between the machining parameter and the subject matter, regenerative chatter occurrence, is exciting to share. This is the primary motivation in pursuing this study.